2011
DOI: 10.1007/s11783-011-0358-7
|View full text |Cite
|
Sign up to set email alerts
|

Hygroscopicity of ambient submicron particles in urban Hangzhou, China

Abstract: In this study, hygroscopicity of size-segregated ambient submicron particles in urban Hangzhou was studied from 28th December 2009 to 18th January 2010, using a hygroscopicity-tandem differential mobility analyzer (H-TDMA). The submicron particles in Hangzhou showed a minor hygroscopic growth at 73% relative humidity (RH), and then grew significantly between 77% and 82% RH. Monomodal distribution accounted for 90% for 30 nm particles, 17% for 50 nm particles, and less than 7% for particles larger than 50 nm at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…[40] A final consideration is that the hygroscopic behavior of particles of mixed composition, containing inorganic species together with soluble organic compounds, can differ from that of single-component aerosols. There is no clear consensus in the literature, with both increases and decreases in DRH values having been reported for mixed aerosols, compared to those containing inorganic substances alone [Choi and Chan, 2002;Miñambres et al, 2010;Wu et al, 2011;Zhang et al, 2011]. The chemical measurements (Table 2) showed that WSOC contributed 66.5%, on average, to the total mass of the soluble aerosol species measured, so that the existence of internal mixtures of inorganic compounds and WSOC could potentially affect aerosol growth rates.…”
Section: Influence Of Aerosol Composition On Water Uptake Capacitymentioning
confidence: 98%
“…[40] A final consideration is that the hygroscopic behavior of particles of mixed composition, containing inorganic species together with soluble organic compounds, can differ from that of single-component aerosols. There is no clear consensus in the literature, with both increases and decreases in DRH values having been reported for mixed aerosols, compared to those containing inorganic substances alone [Choi and Chan, 2002;Miñambres et al, 2010;Wu et al, 2011;Zhang et al, 2011]. The chemical measurements (Table 2) showed that WSOC contributed 66.5%, on average, to the total mass of the soluble aerosol species measured, so that the existence of internal mixtures of inorganic compounds and WSOC could potentially affect aerosol growth rates.…”
Section: Influence Of Aerosol Composition On Water Uptake Capacitymentioning
confidence: 98%
“…Bimodal hygroscopicity distribution was observed for 50-200 nm aerosols, while unimodal hygroscopicity distribution was observed for 30 nm aerosols (Zhang et al, 2011). The average κ values decreased from 0.121 at 30 nm to 0.065 at 80 nm for the low hygroscopic mode, and a further increase in particle size (up to 200 nm) did not lead to significant change in κ values (Zhang et al, 2011). For comparison, the average κ values increased from 0.303 at 30 nm to 0.343 at 80 nm for the more hygroscopic mode, and a further increase in particle size only resulted in a very small increase in κ values.…”
Section: Hangzhoumentioning
confidence: 86%
“…For comparison, the average κ values increased from 0.303 at 30 nm to 0.343 at 80 nm for the more hygroscopic mode, and a further increase in particle size only resulted in a very small increase in κ values. In addition, number fractions of particles in the more hygroscopic mode increased from ∼ 48 % for 30 nm to ∼ 70 % for 100 nm and remained nearly constant for 100-200 nm (Zhang et al, 2011).…”
Section: Hangzhoumentioning
confidence: 93%
See 2 more Smart Citations